2022
DOI: 10.31841/kjems.2022.123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Credit and Liquidity Risks on Bank Stability: Empirical Evidence from Afghanistan

Abstract: This study investigates the effects of liquidity and credit risks on the stability of banks with empirical evidence from the Afghanistan banking sector over the period 2014–2020. The stability of a bank is measured through the dependent variable of its capital adequacy ratio. Credit risk (calculated by the ratio of impaired loans) is included as an independent variable along with liquidity risk. The bank specific factors, namely bank net interest margin, size of the bank, return on assets, loan growth rate, li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The two biggest and most dangerous risks to bank performance and stability, according to banking literature, are credit and LRs. (Hamdi and Hakimi 2019;Reinhart and Rogoff 2011;Boussaada et al 2022;Magwedere and Marozva 2022;Faiz 2022). Strongly documented in the literature focused on the determinants of credit and LRs (Ghenimi et al 2021;Hakimi and Zaghdoudi 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The two biggest and most dangerous risks to bank performance and stability, according to banking literature, are credit and LRs. (Hamdi and Hakimi 2019;Reinhart and Rogoff 2011;Boussaada et al 2022;Magwedere and Marozva 2022;Faiz 2022). Strongly documented in the literature focused on the determinants of credit and LRs (Ghenimi et al 2021;Hakimi and Zaghdoudi 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several empirical studies concluded that the two risks are positively correlated (Cai and Zhang 2017;He and Xiong 2012;Magwedere and Marozva 2022. However, few studies supported either the negative (Cai and Thakor 2008;Wagner 2007;Faiz 2022) or the non-significant effect (Imbierowicz and Rauch 2014). Besides reviewing studies based on the positive or negative effect, the literature on the credit-LR relationships is divided into linear and non-linear analyses.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations